2019
DOI: 10.3390/app9193988
|View full text |Cite
|
Sign up to set email alerts
|

SERS-Active Substrates Nanoengineering Based on e-Beam Evaporated Self-Assembled Silver Films

Abstract: Surface-enhanced Raman spectroscopy (SERS) has been intensely studied as a possible solution in the fields of analytical chemistry and biosensorics for decades. Substantial research has been devoted to engineering signal enhanced SERS-active substrates based on semi-continuous nanostructured silver and gold films, or agglomerates of micro- and nanoparticles in solution. Herein, we demonstrate the high-amplitude spectra of myoglobin precipitated out of ultra-low concentration solutions (below 10 μg/mL) using e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 53 publications
(62 reference statements)
0
27
0
2
Order By: Relevance
“…For 1 μM MB dye, we also observed similar degree of enhancement to that of 1.5, 6, and 7 nm films synthesized by APCVD film. The surface morphology (roughness) usually plays an important role in creation of local hot spots, which leads to even higher enhancement of the Raman signal of the adsorbed analyte [ 42 , 43 ]. Interestingly, for the case of a highly wrinkled surface of 7 nm thick hBN film (with highest surface roughness), we observed similar enhancement of ≈10 4 for MB molecules compared to the flat hBN films.…”
Section: Resultsmentioning
confidence: 99%
“…For 1 μM MB dye, we also observed similar degree of enhancement to that of 1.5, 6, and 7 nm films synthesized by APCVD film. The surface morphology (roughness) usually plays an important role in creation of local hot spots, which leads to even higher enhancement of the Raman signal of the adsorbed analyte [ 42 , 43 ]. Interestingly, for the case of a highly wrinkled surface of 7 nm thick hBN film (with highest surface roughness), we observed similar enhancement of ≈10 4 for MB molecules compared to the flat hBN films.…”
Section: Resultsmentioning
confidence: 99%
“…The SERS largely depends on the type of substrate and its preparation. SERS platform can be designed in the form of colloidal metal solutions as well as thin precipitated or nanometer films, and the most common types of SERS-active substrates showing the largest effects are colloidal silver and gold, and evaporated films of these metals [120][121][122]. In a similar study, Yeh et al showed that by using the synthesized Nowadays, the molecular and immunoassay methods are widely used to detect COVID-19 deploying virus RNA proteins; however, they are not useful for POC applications due to limitations, such as the need for expensive equipment and experienced personnel, as well as the high cost of diagnostic services.…”
Section: Point-of-care Detection Of Sars-cov-2mentioning
confidence: 99%
“…The SERS largely depends on the type of substrate and its preparation. SERS platform can be designed in the form of colloidal metal solutions as well as thin precipitated or nanometer films, and the most common types of SERS-active substrates showing the largest effects are colloidal silver and gold, and evaporated films of these metals [ 120 , 121 , 122 ]. In a similar study, Yeh et al showed that by using the synthesized nitrogen modified carbon nanotubes decorated with Au NPs, virus detection would be very accurate in a short time.…”
Section: Current Diagnostic Techniques For the Detection Of Sars-cmentioning
confidence: 99%
“…Такие пленки могут быть эффективно использованы для изучения и регистрации спектров ГКР биологических аналитов различных типов. Такие подложки были разработаны в [2].…”
Section: Introductionunclassified
“…Было впервые продемонстрировано разделение гликированного и негликированного альбумина на ГКР-активных субстратах на основе самоорганизующихся непрерывных серебряных пленок. Этот тип подложки был ранее предложен в работе [2]. Было показано, что морфология поверхности играет критическую роль в анализе белка, поскольку она обеспечивает достаточный уровень сигнала ГКР от раствора белков с низкой концентрацией.…”
Section: Introductionunclassified